Leisure, family and lifestyle : unemployed young people - Lobo, Francis (Jaipur : Rawat Publications, 2002)
Sociological study of young unemployed in their "late career"; with reference to Western Australia; as part of the methodology of study some workshops were conducted.
Includes bibliographical references (p. [198]-205) and index.
Keywords: YOUTH -- AUSTRALIA -- SOCIAL CONDITIONS; UNEMPLOYED -- AUSTRALIA